A Review of the Benefits and Barriers to Postsecondary Education for Students With Intellectual and Developmental Disabilities. (February 2022) - Lee, Chung Eun; Taylor, Julie Lounds
Postsecondary educational programs (PSEs) are increasingly an option for students with intellectual and developmental disabilities (IDD). This scoping review synthesized research to understand the impacts of these programs for students with IDD and for campus, and barriers to these programs across stages of engagement (exploration, participation, completion). Studies were identified by searching PubMed, PsycINFO, ERIC, and Web of Science databases and reference lists of included articles. Twenty-one studies met inclusion criteria. Multiple benefits were identified for students with IDD and campus. Persistent barriers across all stages of program engagement included lack of funding and lack of collaboration. Barriers specific to stages included lack of knowledge, options, individualized support, integration into campus, and transportation. Implications for research and practice are discussed.